2019
DOI: 10.1002/jaal.1033
|View full text |Cite
|
Sign up to set email alerts
|

Reframing and Repositioning College Readers’ Assumptions About Reading Through Eye Movement Miscue Analysis

Abstract: As one of multiple ways to explore the reading process, eye movement miscue analysis is a tool that provides a continuous record of eye fixations and movements over an entire text, and a record of the oral reading of that text and the miscues (observed responses) that readers produce. The authors present profiles of two successful college readers who doubted their reading efficacy. Using data from eye tracking, miscue analysis, and the retelling, the authors invited the readers to examine their assumptions abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Layering findings from a traditional miscue analysis, the Multidimensional Fluency Scale, RF, and the VIT of EMMA allowed a lens through which a much more complex picture of fluency emerged. Previous EMMA research has supported a transactional perspective of reading and demonstrated that eye movements can provide rich information about readers’ interactions with a text, information that we cannot detect solely using a reader’s verbal output (Flurkey et al, 2008; Porter et al, 2019). In this investigation, the reader’s fluency ebbed and flowed throughout the reading of a passage.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Layering findings from a traditional miscue analysis, the Multidimensional Fluency Scale, RF, and the VIT of EMMA allowed a lens through which a much more complex picture of fluency emerged. Previous EMMA research has supported a transactional perspective of reading and demonstrated that eye movements can provide rich information about readers’ interactions with a text, information that we cannot detect solely using a reader’s verbal output (Flurkey et al, 2008; Porter et al, 2019). In this investigation, the reader’s fluency ebbed and flowed throughout the reading of a passage.…”
Section: Discussionmentioning
confidence: 82%
“…We investigate the variability of fluency in the context of oral reading with one child, through the use of a multiple lens approach, utilizing various data sources and analyses. We apply previously established instruments of fluency assessment (Rasinski, 2004) to reading flow (RF; Flurkey, 1997) and eye movement miscue analysis (EMMA; Flurkey et al, 2008; Nelson et al, 2008; Paulson, 2000; Porter et al, 2019). We use an instrumental case study approach to consider how fluency varies within a whole text and what insight this variability might provide to researchers and professionals in the field of education.…”
mentioning
confidence: 99%
“…Additionally, they learned miscues did not always change the meaning, and they did not need to correct the high-quality miscues for efficiency because it is the reader's text that the reader is understanding (Goodman et al, 2016). Although the previous studies presented findings about non-EL readers (e.g., Kim et al, 2010;Porter et al, 2020), it was powerful for the adult ELs to recognize their eye movements and miscues and shift their reading views.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, the reader who struggled understood the reading process and identified his reading strengths and challenges. Another study found that sharing eye movement and miscue data with adult native speakers helped them unpack their reading process and value their strengths (Porter et al, 2020). However, outside of this study, REMMA has yet been used with adult ELs.…”
Section: Articlementioning
confidence: 90%
“…While those data are numerical in form, many eye‐tracking instruments also produce a real‐time recording of a reader's eye‐movement session with a cursor representing the reader's fixations, the movements of which represents where the reader looked while navigating a section of text. The resulting recording becomes a highly intuitive map of the reading process that can be useful in understanding from a holistic perspective how a reader approached a text (Arya & Liwanag, 2022) and has been informative when working with college readers (see Porter et al., 2020).…”
Section: Introductionmentioning
confidence: 99%